2022
DOI: 10.1371/journal.pone.0263798
|View full text |Cite
|
Sign up to set email alerts
|

Germination and seed persistence of Amaranthus retroflexus and Amaranthus viridis: Two emerging weeds in Australian cotton and other summer crops

Abstract: Redroot pigweed (Amaranthus retroflexus L.) and slender amaranth (Amaranthus viridis L.) are becoming problematic weeds in summer crops, including cotton in Australia. A series of laboratory and field experiments were performed to examine the germination ecology, and seed persistence of two populations of A. retroflexus and A. viridis collected from the Goondiwindi and Gatton regions of Australia. Both populations of A. retroflexus and A. viridis behaved similarly to different environmental conditions. Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Amaranths were also reported as tolerant to low and moderate salinity during germination, although there is a large variability, sometimes even among genotypes within the same species. The seed germination of the noxious weed A. retroflexus from China was higher upon 150 mM NaCl treatment than under control conditions [52], whereas for seeds collected from Queensland (Australia), the germination percentage dropped by 50% at only 100 mM NaCl conditions [53]. Moreover, large varia-tions in germination percentages under salt were reported in cultivars of edible A. cruentus from Benin [26].…”
Section: Discussionmentioning
confidence: 96%
“…Amaranths were also reported as tolerant to low and moderate salinity during germination, although there is a large variability, sometimes even among genotypes within the same species. The seed germination of the noxious weed A. retroflexus from China was higher upon 150 mM NaCl treatment than under control conditions [52], whereas for seeds collected from Queensland (Australia), the germination percentage dropped by 50% at only 100 mM NaCl conditions [53]. Moreover, large varia-tions in germination percentages under salt were reported in cultivars of edible A. cruentus from Benin [26].…”
Section: Discussionmentioning
confidence: 96%
“…Seeds that did not collapse under gentle pressure were considered viable and are hereafter referred to as persistent. Responses to gentle pressure have been used for assessments of weed seed viability (Borza et al 2007;Khan et al 2022), including assessments of seed viability for Palmer amaranth (Korres et al 2018). To our knowledge, previous reports for pressure assessments of seed viability did not include information on the amounts of force applied to individual seeds.…”
Section: Methodsmentioning
confidence: 99%
“…However, reports of similar studies on other Amaranthus species are available. For example, Khan et al (2022) reported that F I G U R E 3 Germination percentage (mean ± standard error of mean) of Amaranthus tuberculatus seeds under the effect of pH levels. The bars with the same lowercase letters are not significantly different according to the Fisher's Least Significant Difference test at a 0.05 level of significance.…”
Section: Effect Of Salinity Levels On Seed Germinationmentioning
confidence: 99%